ArfGAP1 Is a GTPase Activating Protein for LRRK2: Reciprocal Regulation of ArfGAP1 by LRRK2. - Xiong, Y.; Yuan, C.; Chen, R.; Dawson, T.M.; Dawson, V.L. (Journal of Neuroscience, 2012)
Both sporadic and autosomal dominant forms of Parkinson's disease (PD) have been causally linked to mutations in leucine-rich repeat kinase 2 (LRRK2), a large protein with multiple domains. The kinase domain plays an important role in LRRK2-mediated toxicity. Although a number of investigations have focused on LRRK2 kinase activity, less is known about the GTPase function of LRRK2. The activity of GTPases is regulated by GTPase activating proteins (GAPs) and GTP exchange factors. Here, we identify ArfGAP1 as the first GAP for LRRK2. ArfGAP1 binds LRRK2 predominantly via the WD40 and kinase domain of LRRK2, and it increases LRRK2 GTPase activity and regulates LRRK2 toxicity both in vitro and in vivo in Drosophila melanogaster. Unexpectedly, ArfGAP1 is an LRRK2 kinase substrate whose GAP activity is inhibited by LRRK2, whereas wild-type and G2019S LRRK2 autophosphorylation and kinase activity are significantly reduced in the presence of ArfGAP1. Overexpressed ArfGAP1 exhibits toxicity that is reduced by LRRK2 both in vitro and in vivo. ?64-ArfGAP1, a dominant-negative ArfGAP1, and shRNA knockdown of ArfGAP1 reduce LRRK2 toxicity. Thus, LRRK2 and ArfGAP1 reciprocally regulate the activity of each other. Our results provide insight into the basic pathobiology of LRRK2 and indicate an important role for the GTPase domain and ArfGAP1 in LRRK2-mediated toxicity. These data suggest that agents targeted toward regulation of LRRK2 GTP hydrolysis might be therapeutic agents for the treatment of PD.